Low-fouling properties in serum of carboxylic-oligo(ethylene glycol)-based interfaces - Santos, Adriano [UNESP]; Garcia Nicholson, Melany Isabel [UNESP]; Feliciano, Gustavo Troiano [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier B.V., 2021)
In the present work we evaluated the low-fouling feature of a carboxylic-oligo(ethylene glycol) self-assembled monolayer (carboxylic-OEG-SAM) interface using a quartz crystal microbalance with dissipation monitoring (QCM-D). QCM-D measurements allowed us to estimate the amount of protein loading in two different serum dilutions at two different interfaces: bare gold and carboxylic-OEG. The observed amount of protein adsorbed onto bare gold is about twice higher that of carboxylic OEG interface, confirming the low-fouling characteristics of OEG-modified surfaces. Additionally, QCM-D results demonstrated the existence of two protein adsorption regimes, a faster and a slower, with distinct dissipation energies which was modelled by a two-step kinetic model. The faster regime was attributed to the adsorption of proteins into free sites of the carboxylic-OEG-SAM in a rigid binding process, followed by a slower and more viscoelastic adsorption process ascribed to structural conformational changes; this slower step conforms with the filling of remaining free sites associated with the steric hindrance in which protein-protein interactions defines the slower rate constant for the adsorption.
Keywords: Low-fouling interfaces; QCM-D; Molecular dynamics; Protein adsorption; Self-assembled monolayers